100 greatest film scores - Lawson, Matt; MacDonald, Laurence E. (Rowman & Littlefield, 2018)
This book considers the greatest film scores produced over a span of more than 80 years. Each entry includes background information about the film, biographical information about the composer, a concise analysis of the score, and a summary of the score's impact both within the film it accompanies, but also on cinematic history.